15th Pacific Conference on Computer Graphics and Applications (PG'07) 2007
DOI: 10.1109/pg.2007.42
|View full text |Cite
|
Sign up to set email alerts
|

Genus Oblivious Cross Parameterization: Robust Topological Management of Inter-Surface Maps

Abstract: We consider the problem of generating a map between two triangulated meshes, M and M ', with arbitrary and possibly differing genus. This problem has rarely been tackled in its generality. Early schemes considered only topological spheres. Recent algorithms allow inputs with an arbitrary number of tunnels but require M and M ' to have equal genus, mapping tunnel to tunnel. Other schemes which allow more general inputs are not guaranteed to work and the authors do not provide a characterization of the input mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…the functions f and g are Morse functions with the minimal number of critical points, the Jacobi set J(f, g) has the minimal number of loops and contains no BD points. Previously, Bennett et al [2] suggested that given a domain with genus γ the minimal Jacobi set has γ + 1 loops. We disprove this claim by showing that there exist functions f and g on M that give rise to at least one and at most two Jacobi loops.…”
Section: Minimal Jacobi Setsmentioning
confidence: 99%
“…the functions f and g are Morse functions with the minimal number of critical points, the Jacobi set J(f, g) has the minimal number of loops and contains no BD points. Previously, Bennett et al [2] suggested that given a domain with genus γ the minimal Jacobi set has γ + 1 loops. We disprove this claim by showing that there exist functions f and g on M that give rise to at least one and at most two Jacobi loops.…”
Section: Minimal Jacobi Setsmentioning
confidence: 99%
“…Edelsbrunner et al [1] have shown that the Jacobi sets can be used to compute a comparison measure between two scalar functions. Bennett et al [2] have used the Jacobi set to represent tunnels and the silhouette of a mesh, both of which are subsequently used to compute a cross parameterization. Jacobi sets have also been used to track features of time-varying events such as molecular interactions, combustion simulation, etc.…”
Section: Introductionmentioning
confidence: 99%